TANGGUNG JAWAB BORGTOCHT TERHADAP DEBITUR YANG DINYATAKAN PAILIT - Siburian, Churcil; Bachtiar, Maryati; Hasanah, Ulfia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
In the case of bankruptcy when the debtor makes a default or does not repay the debt, the creditor immediately asks for accountability to borgtocht as the guarantor in the absence of debt collection to the debtor. Often direct creditors collect the debt to the guarantor, which is clearly not a debtor. And it happens in bankruptcy law that the guarantor of as a guarantor of debtors debtor bankrupted by its creditor without first seeing the real debtor's property.Borgtocht case which is bankrupted before the debtor performs its responsibility can be seen in the decision Number 212 K / pdt.Sus-bankrupt / 2015 case between PT. Jaya Lestari as underwriter with PT. Rabobank International as a creditor clearly seen that as if indeed creditors blame the insurer of the debtor, whereas previously there was a debtor who must be held accountable.In this case the creditor submits a bankruptcy request against the insurer ie PT. Jaya Lestari. The reason the creditor filed for bankruptcy is because the debtor can not repay the debt that has matured. Because in this case the debtor has an underwriter (borg), then this submission is addressed to the insurer of the debtor, and this penanngung is considered as the debtor responsible for the debts of the principal debtor. Applications for bankruptcy of the creditor are accepted, and the insurer is finally bankrupted. Whereas the creditors should first charge the main debtor as the party who owes.This shows that there are still many who do not know the accountability (borg) in a bankruptcy, so that many guarantors are harmed. Based on the above case, the authors are interested to examine "Borgtocht Borrower's Responsibility to the Debt declared bankrupt".Keywords: Borgtocht, Bankruptcy, Default.